INTEGRASI DESIGN SCIENCE RESEARCH DAN DESIGN THINKING DALAM OPTIMALISASI FITUR SISTEM INFORMASI AKADEMIK (SIAKAD) PRADITA: INTEGRATION OF DESIGN SCIENCE RESEARCH AND DESIGN THINKING IN OPTIMIZING THE FEATURES OF PRADITA'S ACADEMIC INFORMATION SYSTEM (SIAKAD) - Tara Anabel Christy Lianda; Afifah Trista Ayunda (LPPM Universitas Abdurrab, 2026)
This study aims to design and evaluate a new feature prototype in the Pradita Academic Information System (SIAKAD) as an artifact within the context of Design Science Research (DSR), with the goal of improving student satisfaction with academic services. Design Thinking (DT) and DSR methodologies are systematically integrated to develop a user-centered solution validated by empirical data. Qualitative evaluation is conducted through a Heuristic Evaluation (HE) conducted by a user experience (UX) expert, while quantitative evaluation is conducted using the Post-Study System Usability Questionnaire (PSSUQ). The results of this study show improvements in usability and interface quality, with an average PSSUQ score of 2.90, which is included in the